Penile fracture with two ipsilateral corporal tears and delayed presentation: A case report - Rajih, Emad; Alenizi, Abdullah; El-Hakim, Assaad (Canadian Urological Association Journal, 2015)
Although penile fracture is an infrequent injury, it is a welldescribed urologic emergency. It results from the rupture of the tunica albuginea of corpora cavernosa by blunt strain that mandates immediate surgical exploration. Reported cases are usually single tear unless contralateral corporal tear is present. We present a case of 56-year-old with intraoperative findings of two separate tears in the same corpus cavernosum. Clinical presentation was also delayed for 4 days post-injury and repair was performed on day 7. This case accentuates the need for a high index of suspicion to rule out concomitant ipsilateral tear. Delayed repair was possible, and full recovery ensued.